Post-translational Modifications in Regulation of Chloroplast Function: Recent Advances - Grabsztunowicz, Magda; Koskela, Minna M.; Mulo, Paula (Frontiers in Plant Science, 2017)
Post-translational modifications (PTMs) of proteins enable fast modulation of protein function in response to metabolic and environmental changes. Phosphorylation is known to play a major role in regulating distribution of light energy between the Photosystems (PS) I and II (state transitions) and in PSII repair cycle. In addition, thioredoxin-mediated redox regulation of Calvin cycle enzymes has been shown to determine the efficiency of carbon assimilation. Besides these well characterized modifications, recent methodological progress has enabled identification of numerous other types of post-translational modifications in various plant compartments, including chloroplasts. To date, at least N-terminal and Lys acetylation, Lys methylation, Tyr nitration and S-nitrosylation, glutathionylation, sumoylation and glycosylation of chloroplast proteins have been described. These modifications impact DNA replication, control transcriptional efficiency, regulate translational machinery and affect metabolic activities within the chloroplast. Moreover, light reactions of photosynthesis as well as carbon assimilation are regulated at multiple levels by a number of PTMs. It is likely that future studies will reveal novel metabolic pathways to be regulated by PTMs as well as detailed molecular mechanisms of PTM-mediated regulation.